(untitled) (International Journal of Engineering and Computer Science, 2017)
Wireless Sensor Networks has turn out to be an explorative area of research since last few years, due to energy constraints of sensors. Reduction of energy is a vital part of the research in this field. Congestion control is a key problem in mobile ad-hoc and sensor networks. In case of congestion system require more power to deliver data. The standard Transmission Control Protocol congestion control method is not able to handle the special properties of a shared wireless multi-hop channel. In particular the frequent changes of the network topology and the shared nature of the wireless channel pose significant challenges. Many approaches have been proposed to overcome these difficulties. In this paper, we present an overview over Congestion Aware Routing and propose a new protocol to introduce secured transfer of data and avoid loss of low priority packets which is a bottleneck of Congestion Aware Routing.